What are the key ingredients for a successful ecosystem restoration - Louhaichi, Mounir (2024)
The presentation was delivered by Mounir Louhaichi during the IUCN-Dryland Session on "Sustainable Land Management Practices for Resilient Ecosystems in Arid Areas: Case Studies and Lessons Learned" at COP 16, KSA. It discussed the essential components for successful ecosystem restoration and emphasized the importance of understanding historical context, stakeholder perspectives, and socio-cultural dynamics during the planning phase. The presentation advocated for a multi-stakeholder approach that empowered communities, incorporated local knowledge, and addressed specific site conditions. Key messages highlighted the need for effective monitoring and acknowledged that livestock grazing, when managed properly, could be a beneficial tool for ecosystem management. The emphasis was on tailored, context-specific interventions for restoring degraded landscapes.